Information processing and synaptic plasticity at hippocampal mossy fiber terminals - Evstratova, Alesya; Tóth, Katalin (Frontiers in Cellular Neuroscience, 2014)
Granule cells of the dentate gyrus receive cortical information and they transform and transmit this code to the CA3 area via their axons, the mossy fibers. Structural and functional complexity of this network has been extensively studied at various organizational levels. This review is focused on the anatomical and physiological properties of the mossy fiber system. We will discuss the mechanism by which dentate granule cells process signals from single action potentials, short bursts and longer stimuli. Various parameters of synaptic interactions at different target cells such as quantal transmission, short- and long-term plasticity will be summarized. Different types of synaptic contacts formed by mossy fibers have unique sets of rules for information processing during different rates of granule cell activity. We will investigate the complex interactions between key determinants of information transfer between the dentate gyrus and the CA3 area of the hippocampus.